2002
DOI: 10.1002/pola.10361
|View full text |Cite
|
Sign up to set email alerts
|

New synthetic method for aromatic polyketones from bis(arylsilane)s and aromatic dicarboxylic acid chlorides

Abstract: A new synthetic method for aromatic polyketones was developed through Friedel-Crafts polycondensation of bis(arylsilane) monomers with aromatic dicarboxylic acid chlorides. The solution polycondensation of these monomer pairs in the presence of aluminum chloride in 1,2-dichloroethane readily afforded aromatic polyketones having inherent viscosities up to 0.37 dL/g with the elimination of chlorotrimethylsilane. The polycondensation proceeded through aromatic electrophilic ipso substitution, the mechanism of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 20 publications
3
13
1
Order By: Relevance
“…The IR spectra of compounds 2a and 2b exhibited an absorption band at 3057–3058 cm −1 due to aromatic CH stretching and a characteristic carbonyl absorption at 1656–1657 cm −1 . The 13 C NMR spectrum of compound 2a showed 11 peaks and was quite different from that of bis(4‐benzoylphenyl) ether, which had 9 peaks 6. In addition, the 13 C NMR spectrum of compound 2b exhibited 12 peaks as expected.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…The IR spectra of compounds 2a and 2b exhibited an absorption band at 3057–3058 cm −1 due to aromatic CH stretching and a characteristic carbonyl absorption at 1656–1657 cm −1 . The 13 C NMR spectrum of compound 2a showed 11 peaks and was quite different from that of bis(4‐benzoylphenyl) ether, which had 9 peaks 6. In addition, the 13 C NMR spectrum of compound 2b exhibited 12 peaks as expected.…”
Section: Resultsmentioning
confidence: 64%
“…The model reaction was then extended to the polycondensation of the bifunctional monomer pairs, metasubstituted bis(arylsilane)s ( 1a and 1b ) and aromatic dicarboxylic acid chlorides ( 3a – 3c ), under the Friedel–Crafts reaction conditions (Scheme ). The polymerization conditions were selected by reference to those for the aromatic polyketone synthesis with parasubstituted bis(arylsilane)s reported previously 6. Therefore, the polycondensation was carried out in the presence of 3 equiv of aluminum chloride (based on the diacid chloride) in 1,2‐dichloroethane at 20 °C for 24 h. The results of the polycondensation are summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it is generally thought that precipitation terminates chain growth, the increase of molecular weight after precipitation is very interesting phenomenon. It has also been reported that the polymerization medium greatly affects the molecular weight of the resulting PEK, and DCE is a good solvent to prepare the high molecular weight PEK [8]. However, further details of the solvent effect on the precipitation polymerization have not been clarified so far, and few considerations were performed on the polymerization behavior of the precipitation polymerization from the view of the morphology and the structure of the precipitates to our knowledge.…”
Section: Introductionmentioning
confidence: 99%